Adrenomedullin increases the short‐circuit current in the rat prostate: Receptors, chloride channels, the effects of cAMP and calcium ions and implications on fluid secretion. (7th April 2014) - Liao, S. B.; Cheung, K. H.; Cheung, M. P. L.; Wong, P. F.; O, W. S.; Tang, F.
Summary In this study, we have investigated the effects of adrenomedullin on chloride and fluid secretion in the rat prostate. The presence of adrenomedullin (ADM) in rat prostate was confirmed using immunostaining, and the molecular species was determined using gel filtration chromatography coupled with an enzyme‐linked assay for ADM. The effects of ADM on fluid secretion were studied by short‐circuit current technique in a whole mount preparation of the prostate in an Ussing chamber. The results indicated that the ADM level was higher in the ventral than the dorso‐lateral prostate and the major molecular species was the active peptide. ADM increased the short‐circuit current through both the cAMP‐ and calcium‐activated chloride channels in the ventral lobe, but only through the calcium‐activated channels in the dorso‐lateral lobe. These stimulatory effects were blocked by the calcitonin gene‐related peptide (CGRP) receptor antagonist, hCGRP8‐37. We conclude that ADM may regulate prostatic fluid secretion through the chloride channels, which may affect the composition of the seminal plasma bathing the spermatozoa and hence fertility.